To solve for x, we need to isolate the variable on one side of the equation.
First, we can add 7 to both sides of the equation to get rid of the -7.
5x - 7 + 7 = 3 + 7
This simplifies to:
5x = 10
Next, we can divide both sides of the equation by 5 to get rid of the coefficient 5 in front of x.
5x/5 = 10/5
This simplifies to:
x = 2
Therefore, the solution to the equation 5x - 7 = 3 is x = 2.
Solve using inverse operations. 5x-7=3
3 answers
are you sure?
Apologies for the mistake. Let's go through the solution again:
To solve the equation 5x - 7 = 3 using inverse operations:
1. Undo the subtraction of 7 by adding 7 to both sides:
5x - 7 + 7 = 3 + 7
5x = 10
2. Undo the multiplication of x by dividing both sides by 5:
(5x)/5 = 10/5
x = 2
So the correct solution to the equation 5x - 7 = 3 is indeed x = 2.
To solve the equation 5x - 7 = 3 using inverse operations:
1. Undo the subtraction of 7 by adding 7 to both sides:
5x - 7 + 7 = 3 + 7
5x = 10
2. Undo the multiplication of x by dividing both sides by 5:
(5x)/5 = 10/5
x = 2
So the correct solution to the equation 5x - 7 = 3 is indeed x = 2.